Repurposing of Plasminogen: An Orphan Medicinal Product Suitable for SARS-CoV-2 Inhalable Therapeutics - Anna Maria Piras; Ylenia Zambito; Maurizio Lugli; Baldassare Ferro; Paolo Roncucci; Filippo Mori; Alfonso Salvatore; Ester Ascione; Marta Bellini; Roberto Crea (MDPI AG, 2020)
The SARS-CoV-2 infection is associated with pulmonary coagulopathy, which determines the deposition of fibrin in the air spaces and lung parenchyma. The resulting lung lesions compromise patient pulmonary function and increase mortality, or end in permanent lung damage for those who have recovered from the COVID-19 disease. Therefore, local pulmonary fibrinolysis can be efficacious in degrading pre-existing fibrin clots and reducing the conversion of lung lesions into lasting scars. Plasminogen is considered a key player in fibrinolysis processes, and in view of a bench-to-bedside translation, we focused on the aerosolization of an orphan medicinal product (OMP) for ligneous conjunctivitis: human plasminogen (PLG-OMP) eye drops. As such, the sterile and preservative-free solution guarantees the pharmaceutical quality of GMP production and meets the Ph. Eur. requirements of liquid preparations for nebulization. PLG-OMP aerosolization was evaluated both from technological and stability viewpoints, after being submitted to either jet or ultrasonic nebulization. Jet nebulization resulted in a more efficient delivery of an aerosol suitable for pulmonary deposition. The biochemical investigation highlighted substantial protein integrity maintenance with the percentage of native plasminogen band > 90%, in accordance with the quality specifications of PLG-OMP. In a coherent way, the specific activity of plasminogen is maintained within the range 4.8-5.6 IU/mg (PLG-OMP pre-nebulization: 5.0 IU/mg). This is the first study that focuses on the technological and biochemical aspects of aerosolized plasminogen, which could affect both treatment efficacy and clinical dosage delivery. Increasing evidence for the need of local fibrinolytic therapy could merge with the availability of PLG-OMP as an easy handling solution, readily aerosolizable for a fast translation into an extended clinical efficacy assessment in COVID-19 patients.